2004
DOI: 10.1021/jp0464526
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interparticle Interactions upon the Magnetic Properties of CoFe2O4 and MnFe2O4 Nanocrystals

Abstract: The interparticle distance has been systematically varied by controlling the concentration of 8-nm CoFe 2 O 4 or MnFe 2 O 4 spinel ferrite nanocrystals dispersed in eicosane. For both nanoparticulate systems, the blocking temperature decreased with increasing interparticle distance through dilution of nanocrystals, which suggests a decrease in the anisotropy energy barrier E A . The blocking temperature for MnFe 2 O 4 nanoparticles decreased continuously with decreasing nanocrystal concentration in eicosane. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
90
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 36 publications
7
90
0
Order By: Relevance
“…As a general feature, the magnetization decreases with increasing concentration of the nanosized particles. For example, the highest magnetization (M = 22.2 emu g −1 ) corresponds to the most diluted sample (c = 0.25%), whereas the lowest value of magnetization (M = 10.1 emu g and dispersed in eicosane [57]. Although the origin of these discrepancies was not completely elucidated, the variation of the magnetization with the dilution strongly suggests that the interactions between the nanoparticles play an important role in modifying the anisotropy energy barriers of the magnetic system.…”
Section: Resultsmentioning
confidence: 99%
“…As a general feature, the magnetization decreases with increasing concentration of the nanosized particles. For example, the highest magnetization (M = 22.2 emu g −1 ) corresponds to the most diluted sample (c = 0.25%), whereas the lowest value of magnetization (M = 10.1 emu g and dispersed in eicosane [57]. Although the origin of these discrepancies was not completely elucidated, the variation of the magnetization with the dilution strongly suggests that the interactions between the nanoparticles play an important role in modifying the anisotropy energy barriers of the magnetic system.…”
Section: Resultsmentioning
confidence: 99%
“…If nanosized FM particles are to have actual practical applications in areas such as magnetic recording, it is essential to find ways of raising the value of TB to room temperature and above. According to recent studies, exchange bias effects in composite systems have been discovered as a way to overcome the "superparamagnetic limit" of FM nanoparticles [28][29][30], since it has been demonstrated that exchange coupling between the FM and AFM spin systems induces an anisotropy in the FM materials which can leads to substantial increases in T B . Many of the studied exchange-biased systems, which are fabricated by the chemically modifying the surface of a preformed FM core, are composed of homogenous transition metal ferromagnetic cores and a corresponding passive shell, such as Co/CoO [31], Ni/NiO [32], or oxides with different oxidation states as in Fe 3 O 4 /FeO [33] and Mn 3 O 4 /MnO [34].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal decomposition of metal organic precursors is one of the best ways to prepare the high-quality monodisperse nanoparticles in high-boiling point solvent [35][36][37][38][39][40], such as, metal acetylacetonates [35,36], metal carbonyls, etc. The monodisperse Fe 3 O 4 nanoparticles with good crystallinity and uniform size is obtained by thermal decomposition of the iron acetylacetonates dissolved in 1-octadecene at 300 • C using oleic acid and oleyl amine as surfactants under argon atmosphere.…”
Section: Resultsmentioning
confidence: 99%